Potential application of environment-friendly renewable energy system- options for Malaysia - K. Sopian,; M.Y. Othman, B. Yatim,; A.H Shamsuddin, (Environmental Management Society, Malaysia, 2000)
The use of renewable energy resources involves the tapping of natural flows of energy in the environment. If the resource is used in a sustainable fashion, the energy is removed at a rate comparable to that of which energy is being replenished. Malaysia’s agriculture-based economy generates substantial amount of agro-industrial waste, a potential renewable energy resource. It also experiences a high amount of sunshine throughout the year that makes solar energy as another potential energy resource. In addition, wind energy conversion system is suitable for Malaysia’s resort islands. Hydro power is also making impact on the energy supply mix. Malaysia’s heavy dependence on oil is steadily being reduced through substitutions by other primary fuels such as gas and coal. However, renewable energy resources have not contributed much towards the overall energy development. This paper explores the renewable energy supply and assesses its market potential, which can contribute to the mainstream of energy production in the Malaysian energy sector